Penerapan metode Economic Order Quantity (EOQ) dalam persediaan bahan baku untuk meningkatkan efisiensi harga pokok produksi pada UD Gabriela Mebel Manado - Nadeak, Paskah; Saerang, David Paul Elia; Pusung, ⁠Rudy J. (Manajemen Bisnis dan Keuangan Korporat, 2025)
It is crucial to control and determine the correct inventory level to support production efficiency and smooth sales operations. This study analyses the management of raw material inventory using the Economic Order Quantity (EOQ) method to improve cost efficiency in the production process at UD Gabriela Furniture Manado. The study employs a descriptive method with a qualitative approach. The results are clear: the company's raw material purchasing is inefficient. Its current policy results in higher costs, amounting to Rp689,950,000 compared to IDR 687,262,500. If the company implements the Economic Order Quantity method it could achieve monthly savings of IDR 2,687,500.